2021
DOI: 10.1002/cncr.33937
|View full text |Cite
|
Sign up to set email alerts
|

Identifying and describing cancer survivors: Implications for cancer survivorship research and clinical care

Abstract: Background Gathering information directly from cancer survivors has advanced our understanding of the cancer survivorship experience. However, it is unknown whether surveys can distinguish important subgroups of cancer survivors. This study aimed to describe the current landscape of survey questions used to identify and describe cancer survivors in national cross‐sectional studies. Methods Using publicly available databases, the authors identified national cross‐sectional surveys used in the United States with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 31 publications
1
17
0
Order By: Relevance
“…We appreciate the letter by van de Wal and colleagues in response to our recent article describing survey questions used to identify and describe cancer survivors in national cross‐sectional studies 1 . We agree with the authors that we must improve the ease of data collection using self‐reported surveys, expand the capture of relevant information and outcomes, promote the representativeness of participants, and incorporate health and technology literacy.…”
mentioning
confidence: 93%
“…We appreciate the letter by van de Wal and colleagues in response to our recent article describing survey questions used to identify and describe cancer survivors in national cross‐sectional studies 1 . We agree with the authors that we must improve the ease of data collection using self‐reported surveys, expand the capture of relevant information and outcomes, promote the representativeness of participants, and incorporate health and technology literacy.…”
mentioning
confidence: 93%
“…Missing relevant information, such as the cancer type, time from diagnosis, or type(s) of prior or current treatments, is considered an important limitation of most surveys: only 2 of 14 surveys collected all these parameters 1 . In some cases, the collection of limited clinical information might be sufficient to answer a particular research question.…”
mentioning
confidence: 99%
“…The reliability of self‐reported data is also questionable 2 . Doose et al 1 stated that correctly recalling information may vary according to the length of time that has passed between treatment and survey administration. However, other aspects need to be taken into account as well.…”
mentioning
confidence: 99%
See 2 more Smart Citations